MS epoxy structural adhesive and preparation method thereof

By using MS epoxy structural adhesive in lithium battery cell bonding adhesive, combined with the ratio of basic resin and epoxy resin, the existing adhesives have been solved under high humidity and heat conditions, and the improvement of high tensile strength, elongation of break and temperature resistance is achieved, and it is also in line with EU environmental protection standards.

CN119709071APending Publication Date: 2025-03-28GUANGDONG PUSTAR SEALED RAYON CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411882243.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

现有锂电池电池芯的粘接胶在高湿热条件下难以满足高拉伸强度和断裂伸长率的要求,同时耐温性能和环保标准不达标。

Method used

Using MS epoxy structural glue, the tensile strength and elongation of breaking of the glue are improved through the reasonable ratio of components A and B, including the basic resins PPGMS-1 and PPGMS-2, epoxy resin, aminosiloxane and chelating tin catalyst, and the tensile strength and elongation of the glue are improved through the introduction of epoxy.

Benefits of technology

It has achieved high tensile strength and elongation of break under high temperature and high humidity conditions, and complies with EU environmental standards RoHs and REACH, and is suitable for battery bonding adhesives.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005198477180000041
    Figure BDA0005198477180000041
  • Figure BDA0005198477180000051
    Figure BDA0005198477180000051
  • Figure BDA0005198477180000071
    Figure BDA0005198477180000071
Patent Text Reader

Abstract

The invention discloses an MS epoxy structural adhesive and a preparation method thereof, and belongs to the technical field of MS adhesives. The MS epoxy structural adhesive comprises a component A and a component B, the component A comprises basic resin PPGMS-1, basic resin PPGMS-2, amino siloxane, an antioxidant and an epoxy accelerator, the component B comprises epoxy resin and a chelating tin catalyst, and the basic resin PPGMS-1 and the basic resin PPGMS-2 need to meet a certain proportion. The MS epoxy structural adhesive is good in toughness and tensile strength, resistant to temperature and moisture, capable of meeting the environmental protection requirement of European Union and capable of being applied to the field of battery adhesive preparation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of MS adhesives, and in particular relates to a MS epoxy structural adhesive and a preparation method thereof. Background Art

[0002] With the popularization of electrification, electric vehicles, electric ships, electric small aircraft, etc. are gradually being promoted. The promotion of electrification has driven the rapid development of the lithium battery industry. Lithium batteries are explosive materials due to their high risk level. The industry has comprehensive protection for lithium battery cells. There are two main directions, one is to prevent leakage, and the other is to prevent damage. Leakage prevention generally uses PET film coating. On the one hand, damage prevention uses a hard shell to prevent collisions, hard objects and other damage from causing damage to the battery cell. The second is to use elastomers to provide multi-layer protection for the PET film-coated battery cell.

[0003] The industry's adhesives generally protect battery packs in the following aspects: first, use adhesives to bond the PET-coated battery cells to the slots on the bottom plate, which can prevent leakage and provide a buffer for the battery cell group during vehicle vibration; second, place the battery pack on the bottom plate with a fixed slot, and then fill the flame-retardant and thermally conductive potting glue in the gaps of the battery cells, which can not only play a buffering role, but also play a flame-retardant and heat-dissipating function; third, apply elastomer glue under the entire battery pack bottom plate, which can prevent the entire battery pack from generating severe stress with the body frame when the car passes through potholes; fourth, the waterproof seal of the battery shell. Among them, the bonding glue of the battery cell is generally polyurethane glue or two-component silicone rubber. There are still certain disadvantages, such as the poor moisture and heat resistance of polyurethane glue, although silicone rubber has good temperature and moisture resistance. But the problem is that the body strength is too poor, and cracking and degumming often occur during the vehicle vibration process.

[0004] MS epoxy structural adhesive is a new type of hybrid adhesive. It combines the elasticity of MS and can improve the body strength of MS elastomer by adding epoxy components. At the same time, the introduction of epoxy can increase the temperature resistance, flame retardancy and water resistance of MS. After the combination of the two, a high-strength elastomer can be obtained, which can play a good buffering role and has extremely strong bonding force.

[0005] The prior art discloses an epoxy resin modified MS sealant, which is a two-component sealant in which a silane-modified polyether polymer and an epoxy resin are stored separately to increase their stability. However, only the mechanical properties are studied, and the tensile strength and elongation at break are also relatively low, making it difficult to meet the requirements under high humidity and heat conditions.

[0006] Therefore, developing an MS epoxy structural adhesive with high tensile strength and elongation at break, resistance to high temperature and humidity, and compliance with EU environmental protection requirements and its preparation method have important research significance and application value. Summary of the invention

[0007] In order to solve the problems existing in the prior art, the primary purpose of the present invention is to provide a MS epoxy structural adhesive. The MS epoxy structural adhesive provided by the present invention has high tensile strength and elongation at break, is resistant to high temperature and high humidity, and meets the environmental protection requirements of the European Union.

[0008] Another object of the present invention is to provide a method for preparing the above-mentioned MS epoxy structural adhesive.

[0009] Another object of the present invention is to provide an application of the above-mentioned MS epoxy structural adhesive in the field of preparing battery adhesive.

[0010] In order to achieve the above-mentioned invention object, the present invention adopts the following technical scheme:

[0011] The present invention protects a MS epoxy structural adhesive, comprising component A and component B, wherein component A comprises a base resin PPGMS-1, a base resin PPGMS-2, aminosilicone, an antioxidant, and an epoxy accelerator; and component B comprises an epoxy resin and a chelated tin catalyst;

[0012] The base resin PPGMS-1 includes 100 parts of PPG-1000, 40-52 parts of MDI-50, and 40-51 parts of secondary amino-grafted methoxy silane;

[0013] The base resin PPGMS-2 includes 100 parts of PPG-11000-14000, 5-12 parts of MDI-50, and 5-9 parts of secondary amino-grafted methoxy silane;

[0014] The mass ratio of the base resin PPGMS-1 to the base resin PPGMS-2 is 1-2:1-3.

[0015] PPGMS-1 provides a rigid resin and improves the degree of crosslinking. However, based on the problem that the MS glue with only PPGMS-1 in the prior art has poor toughness, low tensile strength and low elongation at break, the present invention adds PPGMS-2 to provide a flexible resin and improve the tensile length and elongation at break. The molecular weight of PPGMS-2 is too low, and due to the excessive functionality, the hardness is too high. Adding too much will cause a decrease in elongation at break. Too high a molecular weight will increase the difficulty of processing, increase costs, and affect the curing speed and mechanical properties of the adhesive.

[0016] On the one hand, in order to improve the tensile length and elongation at break of MS adhesive, a reasonable combination of epoxy resin and MS resin is added to achieve appropriate cross-linking, specifically, the epoxy resin is partially grafted on the aminosilane of MS, which improves the tensile strength of MS epoxy structural adhesive. The epoxy accelerator and chelated tin catalyst work together to make the curing of MS resin and epoxy resin proceed together, and the deep curing speed is faster under the action of the catalyst, which helps to improve the elongation at break.

[0017] On the other hand, the addition of epoxy resin significantly improves the moisture and heat resistance and enhances the overall performance of MS resin. Antioxidants can slow down the weathering and corrosion of colloids caused by high temperature and high humidity.

[0018] The MS epoxy structural adhesive provided by the present invention has high tensile strength and elongation at break, is resistant to high temperature and high humidity, and passes the strict standards of EU environmental protection standards RoHs and REACH, and meets EU environmental protection requirements.

[0019] Specifically, the base resin PPGMS-2 includes PPG-11000-14000, which is a polyether with a molecular weight of 11000-14000.

[0020] Preferably, the PPG-11000-14000 is PPG-12000.

[0021] Preferably, the secondary amino-grafted methoxy silane is selected from at least one of N-n-butyl-3-aminopropyltrimethoxysilane, bis(3-trimethoxysilylpropyl)amine or N-(3-dimethylaminoethyl)-3-aminopropylmethyldimethoxysilane.

[0022] More preferably, the secondary amino-grafted methoxy silane is selected from N-n-butyl-3-aminopropyltrimethoxysilane.

[0023] The reason why the secondary amine-grafted methoxy silane is preferred is that the secondary amine has only one NH bond, and substances without NH bonds do not react. Substances with more NH bonds are prone to excessive cross-linking, self-polymerization, and are not easy to form resins.

[0024] The reason why N-n-butyl-3-aminopropyltrimethoxysilane is preferred is that it is commonly used in the field of structural adhesives and has a low cost.

[0025] Preferably, the component A comprises at least one of a dehydrating agent or fumed silica.

[0026] Preferably, the component B comprises at least one of epoxy diluent, water, calcium carbonate or fumed silica.

[0027] Calcium carbonate and fumed silica play a reinforcing role.

[0028] Preferably, the dehydrating agent is vinyltrimethoxysilane.

[0029] Preferably, the aminosilicone is a primary aminosilicone or a secondary aminosilicone.

[0030] Preferably, the aminosiloxane is aminoethylaminopropyltrimethoxysilane, 1124 One or more of bis(trimethoxysilylpropyl)amine or γ-aminopropyltrimethoxysilane (γ-APS).

[0031] More preferably, the aminosiloxane is aminoethylaminopropyltrimethoxysilane.

[0032] Epoxy accelerators commonly used in the art can be used in the present invention.

[0033] Preferably, the epoxy accelerator is selected from one or more of DMP-30, HDG-A / B epoxy resin curing accelerator, triethylamine or triethanolamine.

[0034] More preferably, the epoxy accelerator is DMP-30.

[0035] Preferably, the aminosilane oligomer is SIVO-203 oligomer, 1146 or One or more of 260.

[0036] More preferably, the aminosilane oligomer is SIVO-203.

[0037] The preferred type of amino oligomer can be partially hydrolyzed under the action of water to form a polymer state of the coupling agent, which can improve the adhesion to the substrate, such as PC material, ABS material, etc., that is, improve the adhesion of the structural adhesive. The single-molecule coupling agent is grafted with the resin chain segment in the glue, and the reaction is relatively regular, and it is difficult to have an internal over-grafting state, and there is no adhesion improvement effect.

[0038] Antioxidants commonly used in the art can be used in the present invention.

[0039] Preferably, the antioxidant is one or more of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate]pentylerythrityl ester or tris(2,4-di-tert-butylphenyl) phosphite.

[0040] Preferably, the weight parts of each component of the above-mentioned component A are:

[0041]

[0042] Preferably, the chelated tin catalyst comprises a mixture of one or more of dibutyltin diacetylacetonate, chelated tin KRA-1 or chelated tin U202H.

[0043] Preferably, the mass ratio of the chelated tin catalyst to the epoxy accelerator is 1:4 to 4:1.

[0044] Preferably, the epoxy diluent is one or both of long straight-chain alkane glycidyl ether and branched-chain alkane glycidyl ether.

[0045] More preferably, the epoxy diluent is one or both of epoxy diluent AGE and 1,6-hexanediol glycidyl ether.

[0046] Specifically, the epoxy diluent AGE is dodeca-tetradecyl glycidyl ether.

[0047] Epoxy diluents contain epoxy groups that can cross-link with curing agents to form a network structure.

[0048] Preferably, the weight parts of each component of the above component B are:

[0049]

[0050] The present invention also provides a method for preparing MS epoxy structural adhesive, comprising the following steps:

[0051] The base resin PPGMS-1 and base resin PPGMS-2 in component A are prepared by dehydration polymerization reaction and addition of silane coupling agent, dispersed and mixed with other components, and the components in component B are dispersed and mixed in proportion to obtain the MS epoxy structural adhesive.

[0052] Preferably, the method for preparing the above-mentioned MS epoxy structural adhesive comprises the following steps:

[0053] S1: Synthesis of base resin PPGMS-1:

[0054] PPG-1000 is dehydrated, MDI-50 is added, stirred for reaction, secondary amino-grafted methoxy silane is added, and vacuum reaction is performed to prepare the base resin PPGMS-1;

[0055] S2: Synthesis of base resin PPGMS-2:

[0056] PPG-11000~14000 is dehydrated, MDI-50 is added, stirred and reacted, secondary amino-grafted methoxy silane is added, and vacuum reaction is performed to prepare the base resin PPGMS-1;

[0057] S3: Preparation of structural adhesive:

[0058] Component A: The above base resin and fumed silica are mixed and dehydrated at high temperature, and a dehydrating agent, aminosiloxane, aminosilane oligomer, antioxidant, and epoxy accelerator are added;

[0059] Component B: Add epoxy resin, fumed silica, calcium carbonate, epoxy diluent, chelated tin catalyst and water.

[0060] Further preferably, the method for preparing the above-mentioned MS epoxy structural adhesive comprises the following steps:

[0061] S10: Synthesis of base resin PPGMS-1:

[0062] S101: PPG-1000 was stirred and reacted in vacuum at 100±10℃ for 90-120min;

[0063] S102: Add MDI-50 at 25-30°C with stirring, raise the temperature to 60-70°C, and stir for 50-70 minutes;

[0064] S103: Add N-n-butyl-3-aminopropyltrimethoxysilane with stirring, and stir at 60-70° C. for 1-2 h;

[0065] S104: Cooling to room temperature, vacuum degassing for 20 to 30 minutes, and preparing the base resin PPGMS-1;

[0066] S20: Synthesis of base resin PPGMS-2:

[0067] S201: PPG-12000 was stirred at 100±10℃ and then vacuum dehydrated;

[0068] S202: Add MDI-50 at 25-30°C with stirring, raise the temperature to 60-70°C, and stir for 50-70 minutes;

[0069] S203: Add N-n-butyl-3-aminopropyltrimethoxysilane with stirring, and stir at 60-70° C. for 1-2 hours;

[0070] S204: Cooling to room temperature, vacuum degassing for 20 to 30 minutes, and preparing a base resin PPGMS-2;

[0071] S30: Preparation of structural adhesive:

[0072] S301: Component A: The above base resin and fumed silica are dispersed and mixed at 100-120°C, vacuum-dehydrated for 2 hours, and cooled to room temperature;

[0073] S302: adding dehydrating agent, aminosilicone, amino oligomer and antioxidant;

[0074] S303: adding epoxy accelerator;

[0075] S304: Component B: add epoxy resin, fumed silica, calcium carbonate, and epoxy diluent;

[0076] S305: Add chelated tin catalyst and water.

[0077] Preferably, the dispersion speed of the double planetary disperser in S30 is 20-30 Hz, the revolution speed is 20-30 Hz, and the vacuum degree is less than -0.09 MPa.

[0078] Preferably, the components are added to S301, S302, S303, S304 and S305 and stirred for 30 to 35 minutes.

[0079] The application of the above-mentioned MS epoxy structural adhesive in the field of preparing battery adhesive is also within the protection scope of the present invention.

[0080] Compared with the prior art, the present invention has the following beneficial effects:

[0081] The component A of the MS epoxy structural adhesive provided by the present invention comprises a base resin PPGMS-1, a base resin PPGMS-2, an aminosilicone, an antioxidant, and an epoxy accelerator, and the component B comprises an epoxy resin and a chelated tin catalyst, wherein the base resin PPGMS-1 and the base resin PPGMS-2 need to meet a certain ratio, and cooperate to improve the mechanical properties and temperature and moisture resistance of the MS epoxy structural adhesive;

[0082] MS epoxy structural adhesive has a tensile strength of more than 8.0MPa and an elongation at break of more than 400%. It is resistant to high temperature and humidity, and has passed the strict standards of EU environmental standards RoHs and REACH. DETAILED DESCRIPTION

[0083] The present invention is further described below in conjunction with examples. These examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples that do not specify specific conditions are usually carried out according to conventional conditions in the art or according to the conditions recommended by the manufacturer; the raw materials, reagents, etc. used, unless otherwise specified, are all raw materials and reagents that can be obtained from commercial channels such as conventional markets. Any non-substantial changes and substitutions made by those skilled in the art on the basis of the present invention belong to the scope of protection claimed by the present invention.

[0084] The performance test methods and standards of the MS epoxy structural adhesives of the embodiments and comparative examples of the present invention are as follows:

[0085] (1) Tensile strength and elongation at break

[0086] The determination of tensile strength and elongation at break refers to the standard GB / T 528-2009 Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber.

[0087] (2) Tensile shear strength

[0088] The determination of tensile shear strength refers to the standard GB / T 7124-2008 Determination of tensile shear strength of adhesives.

[0089] (3) Shear strength after aging

[0090] The aging performance refers to the standard GB / T 35489-2017 Adhesive Aging Conditions Guide, and the shear strength after aging is determined according to the standard GB / T 7124-2008 Determination of Adhesive Tensile Shear Strength.

[0091] (4) High temperature and high humidity aging double 85 1000h

[0092] That is, long-term storage for 1000 hours under high temperature 85°C and humidity 85% RH conditions to characterize the mechanical properties of the material after long-term use.

[0093] Embodiments 1 to 5

[0094] Example 1 A MS epoxy structural adhesive and its preparation method

[0095] Table 1 Basic resin ratio of Example 1

[0096]

[0097] Table 2 Proportions of MS epoxy structural adhesive of Example 1

[0098]

[0099]

[0100] S10: Synthesis of base resin PPGMS-1

[0101] S101: Add PPG-1000 to a vacuum reactor, control the stirring speed to 250 rpm / min, heat to 100°C, and vacuum dehydrate for 100 min;

[0102] S102: Add cooling water to cool the material temperature to 20°C, control the stirring speed to 250 rpm / min, add MDI-50 at one time, slowly increase the temperature to 65°C, and stir at 250 rpm / min for 60 minutes;

[0103] S103: Control the stirring rate to 250 rpm / min, add N-n-butyl-3-aminopropyltrimethoxysilane all at once, maintain the temperature at 65° C., and stir at 250 rpm / min for 1.5 h;

[0104] S104: Cool to room temperature, vacuum degassing for 25 minutes, and prepare the base resin PPGMS-1;

[0105] S20: Synthesis of base resin PPGMS-2

[0106] S201: Add PPG-12000 to a vacuum reactor, control the stirring speed to 250 rpm / min, heat to 100°C, and vacuum dehydrate for 100 minutes;

[0107] S202: Cooling water is introduced to cool the material temperature to 25°C, the stirring speed is controlled to 250 rpm / min, MDI-50 is added at one time, the temperature is slowly raised to 65°C, and stirring is performed at 250 rpm / min for 60 minutes;

[0108] S203: Control the stirring rate to 250 rpm / min, add N-n-butyl-3-aminopropyltrimethoxysilane once, maintain the temperature at 65° C., and stir at 250 rpm / min for 1.5 h;

[0109] S204: Cool to room temperature, vacuum degassing for 25 minutes, and prepare the base resin PPGMS-2;

[0110] S30: Preparation of glue

[0111] S301: Preparation of component A: Add the above resins PPGMS-1 and PPGMS-2 and fumed silica into a double planetary disperser, control the temperature to 110°C, and the vacuum degree to be less than or equal to -0.09MPa, and control the scraping speed to 25Hz and the dispersion speed to 25Hz. Vacuum dehydration for 2 hours, and then cool to room temperature;

[0112] S302: Add vinyl trimethoxysilane, aminoethyl aminopropyl trimethoxysilane, SIVO-203 oligomer, and antioxidant, control the scraping speed to 25 Hz and the dispersion speed to 25 Hz, and stir for 30 minutes under the condition of vacuum degree less than -0.09 MPa;

[0113] S303: adding epoxy accelerator, controlling the scraping speed to 25 Hz and the dispersion speed to 25 Hz, stirring for 30 min under the condition of vacuum degree less than -0.09 MPa to prepare glue A;

[0114] S304: Preparation of component B: Add E51 epoxy resin, fumed silica, calcium carbonate, and epoxy diluent AGE into a double planetary disperser, control the scraping speed to 25 Hz and the dispersion speed to 25 Hz, and stir for 30 minutes under a vacuum degree of less than -0.09 MPa;

[0115] S305: Add water and organic tin catalyst, control the scraping speed to 25Hz and the dispersion speed to 25Hz, and stir for 30 minutes under the condition of vacuum degree less than -0.09MPa to prepare B glue.

[0116] Example 2 A MS epoxy structural adhesive and its preparation method

[0117] The experimental method and the basic resin components are the same as those in Example 1, except for the following:

[0118] Table 3 Basic resin ratio of Example 2

[0119]

[0120]

[0121] Example 3 A MS epoxy structural adhesive and its preparation method

[0122] The experimental method and the basic resin components are the same as those in Example 1, except for the following differences:

[0123] Table 4 Basic resin ratio of Example 3

[0124]

[0125]

[0126] Example 4 A MS epoxy structural adhesive and its preparation method

[0127] The experimental method and the base resin components are the same as those in Example 1, except that the base resin raw material of the base resin PPGMS-2 used is PPG-11000.

[0128] Example 5 A MS epoxy structural adhesive and its preparation method

[0129] The experimental method and the base resin components are the same as those in Example 1, except that the base resin raw material of the base resin PPGMS-2 used is PPG-14000.

[0130] Table 5 Test results of Examples 1 to 5:

[0131]

[0132]

[0133] Comparative Examples 1 to 6

[0134] Comparative Example 1 A MS epoxy structural adhesive and its preparation method

[0135] The experimental scheme is the same as that of Example 1, except that the raw material of the base resin PPGMS-2 is PPG-10000.

[0136] Comparative Example 2 A MS epoxy structural adhesive and its preparation method

[0137] The experimental scheme is the same as that of Example 1, except that the raw material of the base resin PPGMS-2 is PPG-15000.

[0138] Comparative Example 3: A MS epoxy structural adhesive and its preparation method

[0139] The experimental scheme is the same as Example 1, except that only the base resin PPGMS-1 is used, and the base resin PPGMS-2 is not added.

[0140] Comparative Example 4: A MS epoxy structural adhesive and a preparation method thereof

[0141] The experimental scheme is the same as Example 1, except that aminosilicone is not added.

[0142] Comparative Example 5: A MS epoxy structural adhesive and a preparation method thereof

[0143] The experimental scheme is the same as that of Example 1, except that the chelated tin catalyst and the epoxy accelerator are not added.

[0144] Comparative Example 6: A MS epoxy structural adhesive and its preparation method

[0145] The experimental scheme is the same as that of Example 1, except that no chelated tin catalyst is added.

[0146] Table 6 Experimental results of each comparative example

[0147]

[0148]

[0149] From the above test results, it can be seen that embodiments 1 to 5 can achieve an elongation of 400% and a tensile strength of more than 8.0 MPa. They also have good adhesion and aging resistance. They can be used for a long time under high temperature and high humidity, high and low temperature, or extremely high temperature conditions. Among them, embodiment 1 has the best effect.

[0150] Comparative Example 1 uses PPG-10000 to replace PPG-12000 in the base resin PPGMS-2. The functionality is too high, resulting in too high hardness, and both tensile strength and elongation at break are reduced; Comparative Example 2 uses PPG-15000 to replace PPG-12000 in the base resin PPGMS-2. The molecular weight is too large, resulting in a decrease in comprehensive performance; Comparative Example 3 does not add the base resin PPGMS-2, and the tensile strength and elongation at break are greatly reduced, indicating that the base resin PPGMS-2 mainly affects the toughness of the MS epoxy structural adhesive; Comparative Example 4 does not add aminosiloxane, and the epoxy group cannot be grafted onto the MS reaction body, which will cause the role of epoxy in it to be only equivalent to a plasticizer, and the elongation will be greatly improved, but the strength will be greatly reduced, and the temperature resistance will also be reduced because the epoxy does not participate in the reaction. The temperature resistance of MS cannot reach 150°C, and the aging performance will be seriously reduced; Comparative Examples 5 and 6 do not use chelated tin catalysts and epoxy accelerators, indicating that the two have a synergistic effect and can improve the mechanical properties.

[0151] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A MS epoxy structural adhesive, characterized in that: The invention comprises component A and component B, wherein component A comprises base resin PPGMS-1, base resin PPGMS-2, aminosilicone, antioxidant and epoxy accelerator; and component B comprises epoxy resin, epoxy diluent and chelated tin catalyst; The base resin PPGMS-1 includes 100 parts of PPG-1000, 40-52 parts of MDI-50, and 40-51 parts of secondary amino-grafted methoxy silane; The base resin PPGMS-2 includes 100 parts of PPG-11000-14000, 5-12 parts of MDI-50, and 5-9 parts of secondary amino-grafted methoxy silane; The mass ratio of the base resin PPGMS-1 to the base resin PPGMS-2 is 1-2:1-3.

2. The MS epoxy structural adhesive according to claim 1, characterized in that: The component A includes at least one of a dehydrating agent or fumed silica.

3. The MS epoxy structural adhesive according to claim 1, characterized in that: The component B includes at least one of water, calcium carbonate or fumed silica.

4. The MS epoxy structural adhesive according to claim 1, characterized in that: The secondary amino-grafted methoxy silane is selected from at least one of N-n-butyl-3-aminopropyltrimethoxysilane, bis(3-trimethoxysilylpropyl)amine and N-(3-dimethylaminoethyl)-3-aminopropylmethyldimethoxysilane.

5. The MS epoxy structural adhesive according to claim 1, characterized in that: The mass ratio of the chelated tin catalyst to the epoxy accelerator in the component B is 1:4 to 4:

1.

6. The MS epoxy structural adhesive according to claim 1, characterized in that: The chelated tin catalyst includes one or more mixtures of dibutyltin diacetylacetonate, chelated tin KRA-1 or chelated tin U202H.

7. The MS epoxy structural adhesive according to claim 1, characterized in that: The aminosiloxane is one or both of primary aminosiloxane and secondary aminosiloxane.

8. The method for preparing the MS epoxy structural adhesive according to any one of claims 1 to 7, characterized in that: The following steps are involved: The base resin PPGMS-1 and base resin PPGMS-2 in component A are prepared by vacuum dehydration polymerization reaction and adding silane coupling agent, dispersed and mixed with other components, and the components in component B are dispersed and mixed in proportion to obtain the MS epoxy structural adhesive.

9. The method for preparing the MS epoxy structural adhesive according to claim 8, characterized in that: The specific steps include: S1: Synthesis of base resin PPGMS-1: PPG-1000 is dehydrated, MDI-50 is added, stirred for reaction, secondary amino-grafted methoxy silane is added, and vacuum reaction is performed to prepare the base resin PPGMS-1; S2: Synthesis of base resin PPGMS-2: PPG-11000~14000 is dehydrated, MDI-50 is added, stirred and reacted, secondary amino-grafted methoxy silane is added, and vacuum reaction is performed to prepare the base resin PPGMS-1; S3: Preparation of structural adhesive: Component A: The above base resin and fumed silica are mixed and dehydrated at high temperature, and a dehydrating agent, aminosiloxane, aminosilane oligomer, antioxidant, and epoxy accelerator are added; Component B: Add epoxy resin, fumed silica, calcium carbonate, epoxy diluent, chelated tin catalyst and water.

10. Use of the MS epoxy structural adhesive according to any one of claims 1 to 7 in the preparation of battery adhesives.